Nile Tilapia Prefer Water Hyacinth as Structural Enrichment Regardless of Stocking Density - Neto, João Favero [UNESP]; Maia, Caroline Marques [UNESP]; de Oliveira, Rogério [UNESP]; Giaquinto, Percilia Cardoso [UNESP] (Taylor & Francis, 2025)
In this study, we investigated whether Nile tilapia (Oreochromis niloticus), a commonly farmed species worldwide, prefer artificial water hyacinth - easy-to-build and inexpensive - as a structural enrichment by investigating if different common farm stocking densities affect such response. We tested juveniles under three stocking densities (12, 16, or 20 fish per aquarium) in both the absence (control groups) and presence (artificial hyacinth treatments) of the structural enrichment for 6 weeks. We filmed fish every week, both when the hyacinth was spread and when it was concentrated in one aquarium section. We then analyzed their preference responses based on the number of fish recorded in each section. Nile tilapia juveniles preferred artificial hyacinth as a structural enrichment, a strong response that may override an initial preference for another area. Although all tested stocking densities showed a preference for the artificial hyacinth, the intensity of this response was stronger at the highest density. These findings indicate that artificial hyacinth is a highly preferred structural enrichment for Nile tilapia juveniles and should be implemented under farming conditions, particularly at higher stocking densities.